2007
DOI: 10.1002/ibd.20020
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis about mechanisms through which nicotine might exert its effect on the interdependence of inflammation and gut barrier function in ulcerative colitis

Abstract: Ulcerative colitis (UC) is characterized by impairment of the epithelial barrier and the formation of ulcer-type lesions, which result in local leaks and generalized alterations of mucosal tight junctions. Ultimately, this results in increased basal permeability. Although disruption of the epithelial barrier in the gut is a hallmark of inflammatory bowel disease and intestinal infections, it remains unclear whether barrier breakdown is an initiating event of UC or rather a consequence of an underlying inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 101 publications
(75 reference statements)
3
41
0
2
Order By: Relevance
“…4 Intermittent smokers have often been reported to experience symptomatic exacerbation during periods of nonsmoking and alleviation of symptoms on recommencement of smoking. 2,5,6,15,20 The observation that heavier smokers who quit smoking are more susceptible to the rebound effect of developing UC, compared to lighter smokers, also corroborates the notion of a dose-dependent relationship. 6,9,10,16 Current smokers with UC have been found to have less relapses, 33 require fewer hospitalisations 1,6,24,34,35 and demonstrate a reduced need for oral corticosteroid and immunosuppressant therapy for their disease, compared to ex-smokers and nonsmokers with UC.…”
Section: 21supporting
confidence: 57%
See 4 more Smart Citations
“…4 Intermittent smokers have often been reported to experience symptomatic exacerbation during periods of nonsmoking and alleviation of symptoms on recommencement of smoking. 2,5,6,15,20 The observation that heavier smokers who quit smoking are more susceptible to the rebound effect of developing UC, compared to lighter smokers, also corroborates the notion of a dose-dependent relationship. 6,9,10,16 Current smokers with UC have been found to have less relapses, 33 require fewer hospitalisations 1,6,24,34,35 and demonstrate a reduced need for oral corticosteroid and immunosuppressant therapy for their disease, compared to ex-smokers and nonsmokers with UC.…”
Section: 21supporting
confidence: 57%
“…6,35 Those patients who quit smoking after diagnosis of UC often experience an exacerbation in their disease course, and have been uniformly shown to have increased hospitalisation rates and need for oral corticosteroids and immunosuppressants. 1,2,6,24,34,36 It remains divided as to whether smoking reduces the rate of surgery required in UC, particularly colectomy. Fraga et al 11 found that nonsmokers and especially exsmokers underwent surgery for their UC more frequently than current smokers.…”
Section: 21mentioning
confidence: 99%
See 3 more Smart Citations